2018
DOI: 10.1186/s13052-018-0467-z
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity, ventricular septal defect and dysmorphisms are independent predictors of pathogenic copy number variants: a retrospective study on array-CGH results and phenotypical features of 293 children with neurodevelopmental disorders and/or multiple congenital anomalies

Abstract: BackgroundSince 2010, array-CGH (aCGH) has been the first-tier test in the diagnostic approach of children with neurodevelopmental disorders (NDD) or multiple congenital anomalies (MCA) of unknown origin. Its broad application led to the detection of numerous variants of uncertain clinical significance (VOUS). How to appropriately interpret aCGH results represents a challenge for the clinician.MethodWe present a retrospective study on 293 patients with age range 1 month - 29 years (median 7 years) with NDD and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 29 publications
4
18
0
1
Order By: Relevance
“…; Maini et al . ). Two studies found an association with congenital heart diseases (Shoukier et al .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…; Maini et al . ). Two studies found an association with congenital heart diseases (Shoukier et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Maini et al . ). Two studies pointed to hypotonia as a significant feature (Caballero Pérez et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations